Catalytic Synergies in Bimetallic RuPt Single–Atom Catalysts via Speciation Control (Adv. Funct. Mater. 52/2022). (23rd December 2022) - Giulimondi, Vera; Ruiz–Ferrando, Andrea; Clark, Adam H.; Kaiser, Selina K.; Krumeich, Frank; Martín, Antonio J.; López, Núria; Pérez–Ramírez, Javier
Abstract : Bimetallic Single Atom Catalysts In article number 2206513, Javier Pérez–Ramírez, Núria López and co‐workers investigate cooperativity mechanisms between fully isolated Ru and Pt atoms via the hydrogen evolution reaction, demonstrating that catalytic synergies can arise in the absence of direct metal‐metal interactions. By selectively occupying the most energetically favorable cavities in the carbon host, Pt atoms drive Ru atoms to assume a distinct, more active configuration.